Pemanfaatan Eucheuma cottonii dan Sargassum crassifolium Dalam Cookies Sagu Untuk Meningkatkan Kadar Iodium Tikus (Rattus novergicus) - Zasendy Rehena; Lydia M. Ivakdalam (Sangia Publishing, 2018)
Disorders due to iodine deficiency (GAKI) are very serious nutrit ional problems, because they affect the survival and quality of human resources. The effect that is well known to people due to lack of iodine is goiter, suffering from mental disability, namely midget, mute, deafness, and mental disorders. Central Maluku Regency has a very high IDD prevalence rate, which is 33.39%. The strategy is to reduce the search for local food alternatives such as seaweed. Seaweed contains high iodine and can be consumed to prevent iodine deficiency. Central Maluku Regency has abundant and high quality seaweed, but the level of consumption directly by the people as food is still low, thus it is necessary to develop food technology that utilizes seaweed to produce snack / snack products such as cookies. Cookies are generally made from raw flour but can be replaced by using sago flour which is rich in carbohydrates (starch). The purpose of this study was to determine the effect of the type and concentration of seaweed in sago cookies on iodine levels of rats (Rattus norvegicus). The results showed that rats given iodine standard rations had iodine levels with moderate deficiency, and mice given adequate iodine ration had normal iodine levels. The results also showed that the administration of ration cookies containing Sargassum crassifolium 20%, 30%, and 40%, as well as Eucheuma cottonii 30% and 40% could increase rat iodine levels to be optimal. Hypothesis test results showed that the treatment of seaweed type and concentration in the ration of cookies had a significant effect on rat iodine levels. The interaction of types of Sargassum crassifolium 40% was more influential in increasing rat iodine levels. Based on the results of this study it is recommended: Cultivation needs to be developed especially on the types of Eucheuma cottonii and Sargassum crassifoliumin the Central Maluku Regency.Disorders due to iodine deficiency (GAKI) are very serious nutritional problems, because they affectthe survival and quality of human resources. The effect that is well known to people due to lack of iodine isgoiter, suffering from mental disability, namely midget, mute, deafness, and mental disorders. Central MalukuRegency has a very high IDD prevalence rate, which is 33.39%. Thestrategy is to reduce the search for localfood alternatives such as seaweed. Seaweed contains high iodine and can be consumed to prevent iodinedeficiency. Central Maluku Regency has abundant and high quality seaweed, but the level of consumptiondirectly by the people as food is still low, thus it is necessary to develop food technology that utilizes seaweed toproduce snack / snack products such as cookies. Cookies are generally made from raw flour but can be replacedby using sago flour which is rich in carbohydrates (starch). The purpose of this study was to determine theeffect of the type and concentration of seaweed in sago cookies on iodine levels of rats (Rattus norvegicus). Theresults showed that rats given iodine standard rations had iodine levels with moderate deficiency, and micegiven adequate iodine ration had normal iodine levels. The results alsoshowed that the administration of rationcookies containing Sargassum crassifolium 20%, 30%, and 40%, as well as Eucheuma cottonii 30% and 40%could increase rat iodine levels to be optimal. Hypothesis test results showed that the treatment of seaweed typeand concentration in the ration of cookies had a significant effect onrat iodine levels. The interaction of types ofSargassum crassifolium 40% was more influential in increasing rat iodine levels. Based on the results of thisstudy it is recommended: Cultivation needs to be developed especially on the types of Eucheuma cottonii andSargassum crassifolium in the Central Maluku Regency.